EKSPLORASI KESULITAN MEMBACA PERMULAAN SISWA KELAS 1 SEKOLAH DASAR PADA KURIKULUM MERDEKA - Harini, Rochmimah; Subrata, Heru; Muhimmah, Hitta Alfi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Abstract The purpose of this research is to explain the beginning reading problems faced by students in grade 1 elementary school and identify the factors that contribute to these problems. This research is qualitative and uses descriptive methods. This research uses observation, interviews and documentation to collect data. The research subjects were teachers and first grade students. Data was collected through observation and interviews. Thematic analysis utilizes triangulation. The results showed that students in grade 1 of elementary school initially experienced reading difficulties because they had difficulty reading consonant combinations, distinguishing almost identical letters, and reading fluently. Difficulty starting early reading is caused by a number of factors. These include poor initial cognitive abilities, students' decreased interest in starting to read, students' lack of motivation to do so, and lack of parental attention. So it can be said that class I students at SDN Bringinbendo 2 still have difficulty starting to read. It is anticipated that this research will have implications for increasing students' early reading challenges.